PENGARUH LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR CAMAT ANGGANA KABUPATEN KUTAI KARTANEGARA - Setiawan, Wiwit (PREDIKSI, 2012)
This Research target is to known environment work to give the impact to spirit of officer Job. Therefore to get this matter is writer do research [in] Office of Sub-Regency Chief of Anggana of Regency of Kutai Kartanegara.The search will know and look for relation of two variable with analysing result of research by using random technicsly [is] toss 50% from 48 people become 24 officer.  To prove there are not influence between second variable hence writer use the formula of Correlation Moment. Pursuant to data analysis and hypothesis examination, knowable hence relation between  environment work and spirit of Officer jobat  Office of Sub-Regency Chief of Anggana of Regency of Kutai Kartanegara is  good enough.